In situ synthesized BSA capped gold nanoparticles: effective carrier of anticancer drug methotrexate to MCF-7 breast cancer cells - Murawala, Priyanka; Tirmale, Amruta; Shiras, Anjali; Bhagavatula L. V. Prasad (Materials Science & Engineering C-Materials For Biological Applications, 2014)
The proficiency of MTX loaded BSA capped gold nanoparticles (Au-BSA-MTX) in inhibiting the proliferation of breast cancer cells MCF-7 as compared to the free drug Methotrexate (MTX) is demonstrated based on MTT and Ki-67 proliferation assays. In addition, DNA ladder gel electrophoresis studies, flow cytometry and TUNEL assay confirmed the induction of apoptosis by MTX and Au-BSA-MTX in MCF-7 cells. Notably, Au-BSA-MTX: was found to have higher cytotoxicity on MCF-7 cells compared with an equivalent dose of free MTX. The enhanced activity is attributed to the preferential uptake of Au-BSA-MTX particles by MCF-7 cells due to the presence of BSA that acts as a source of nutrient and energy to the rapidly proliferating MCF-7 cells. Moreover, the targeting ability of the drug MTX to the over expressed folate receptors on MCF-7 cells also contributes to the enhanced uptake and activity. Taken together, these results unveil that Au-BSA-MTX could be more effective than free drug for cancer treatment. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Apoptosis; Bovine serum albumin; Cancer therapy; Cytotoxicity; Dual active agents; gold nanoparticles

Dual inhibition of AXL and MER kinase: scope for lung and breast cancer therapeutics - Sathe, Balaji Dashrath; Kumari, Pratibha; Kumar, Hemant; Mane, Madhav Shivaji; Mudududdla, Ramesh; Baell, Jonathan; Kumar, Roshan; Singh, Shareen; Pawar, D. K.; Kommi, Damodara N.; Bushi, Ganesh; Pathak, Prateek; et al. (Bioorganic Chemistry, 2025)
Cancer cells use multiple survival pathways for continuous proliferation, survival, and growth. Recent anticancer drug discovery commonly focuses on a single target that maintains key cancer cell survival mechanisms, where typically, this is a cellular enzyme that inhibits DNA replication, inducing cell damage and apoptosis. Since drugs that act on a single target may be more susceptible to the development of resistance, the search for polypharmacotherapeutics is becoming increasingly popular to defeat drug-resistant cancer cells. Receptor tyrosine kinases (RTKs) family members, AXL and MER, have been identified as important cancer targets and found to be overexpressed and associated with various forms of cancers, such as lung and breast cancers. This review has focused on the dual inhibition of AXL and MER kinases as a strategy for treating lung and breast cancer. The roles of these two kinases in non-small cell lung cancer (NSCLC) are such that dual inhibition would be therapeutically complementary, with MER inhibition more fully blocking tumor growth while AXL inhibition encourages chemosensitivity. Hence, treatment strategies targeting both of these RTKs may be more effective and beneficial than singly targeted agents, and a dual AXL/MER inhibitor is a potential therapy for NSCLC along with breast cancer. This review highlights the preclinical and clinical development of dual AXL and MER kinase inhibitors as lung and breast cancer treatments and the prospects for their future progression.
Keywords: AXL; Breast cancer; Cancer therapy; MER; Multi-kinase inhibitors; NSCLC targeted therapy